The Idea of the American South, 1920-1941 - O'Brien, Michael (Johns Hopkins University Press, 2019)
Originally published in 1979. The idea of the "South" has its roots in Romanticism and American culture of the nineteenth century. This study by Michael O'Brien analyzes how the idea of a unique Southern consciousness endured into the twentieth century and how it affected the lives of prominent white Southern intellectuals. Individual chapters treat Howard Odum, John Donald Wade, John Crowe Ransom, Allen Tate, Frank Owsley, and Donald Davidson. The chapters trace each man's growing need for the idea of the South-how each defined it and how far each was able to sustain the idea as an element of social analysis. The Idea of the American South moves the debate over Southern identity from speculative essays about the "central theme" of Southern history and, by implication, past the restricted perception that race relations are a sufficient key to understanding the history of Southern identity.